(3TQM cJGH SjHhjgs - (3Ydj Hf YjSi Hf Ydj Hf YHO Gddg, CHh GdMSf GdQeGfj , J (B384 (3g`s; (3YeQh Hf YKeGf Hf bfHQ GdMGQKj HGdhdGA, CHh HTQ, GdedbH SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3jHJOF HPcQ GdTGgO ai bhd ZjdGf (B[ (3ef HGH Cda dhUd(B] (3OY PG hYLd PG hCdMbfG HOd HGdTMe EfG bO eddfGg HNd s
(3Vef eLehY , JQJjHgG (B: (3GdNGeSs
(3jdGMX Gf eLdOGJ fSNI ajV Gddg GdePchQI eJJGdjI Edi CfgG JfbU GdeLdO GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs